Social and Psychosocial Impacts for Refugees Post Conflict Between Sunni - Shia in Sampang Madura - Hazim Hazim (Psikologia : Jurnal Psikologi, 2015)
Horizontal conflicts involving religious issues in Indonesia is still very dominant. The conflict between Sunni and Shia in Sampang Madura is the one case of the large impact. the case that occurred on August 26, 2012 has caused in one person died, dozens of people were injured, dozens of homes burned and hundreds of Shias were evacuated. This phenomenon has encouraged me to analyze the psychosocial and social impacts experienced by refugees. This research was focused to the background of horizontal conflict that occured between Sunni and Shia in Sampang, Madura; Conflict resolution efforts, the psychosocial and social impacts for Refugees Shi'ites in Rusun Puspa Agro Jemundo Sidoarjo? This study has used descriptive qualitative. The subject of the research was focused on Shiites who has been evacuating in Jemundo Sidoarjo. The results of this study showed that the conflict was influenced by many factors: ideological, family conflict, economic motive, and local politics. The conflict resolution has been conducted in several stages: stages of de-escalation; stages of humanitarian intervention and political negotiations; stages of problem solving approach; and the last, Peace of building stages; which includes the transition, reconciliation, and consolidation. The social impacts of refugees in Jemundo Sidoarjo were Loss of residence; Loss of livelihood sources; created a dependency with others; For children, they can not access a proper education as well as have been experiencing disorders of psychological development; The refugees have not have basic freedoms: Limited access to health social services; Moreover, there will be impoverishment in the long term.